The LRRK2 R1628P Variant Plays a Protective Role in Han Chinese Population with Alzheimer's Disease. (20th February 2013) - Li, Hong‐Lei; Lu, Shen‐Ji; Sun, Yi‐Min; Guo, Qi‐Hao; Sadovnick, Adele Dessa; Wu, Zhi‐Ying
Summary Aims Alzheimer's disease (AD) and Parkinson's disease (PD) are the most prevalent neurodegenerative disorders that may share some overlapping etiologies. Mutations within leucine‐rich repeat kinase 2 (LRRK2) have been reported to be responsible for PD, and the location of LRRK2 is within a linkage peak for sporadic AD (SAD). The aim of this study was to investigate two Asian‐specific LRRK2 variants, R1628P and G2385R, with the association of Han Chinese SAD. Methods Genotyping of R1628P and G2385R was performed by PCR‐restriction fragment length polymorphism (RFLP) analysis in 390 patients with SAD and 545 unrelated age‐ and sex‐matched healthy controls. Results The frequency of the C allele within R1628P was more than three times higher in control group (1.7%) than in patients with SAD (0.5%) (OR 0.264; 95% CI, 0.088–0.792, P = 0.018). After stratification by the presence of one or two apolipoprotein E ε4 alleles, the protective effect becomes stronger (ε44: OR 0.028; 95% CI, 0.003–0.303, P = 0.003; ε4: OR 0.104; 95% CI, 0.013–0.818, P = 0.031). However, no difference was found in G2385R variant. Conclusion Our study suggested that R1628P variant within LRRK2 plays a protective role in Han Chinese population with SAD and such effect has an interaction with the APOE genotype.